Beisbol en abril y otros cuentos - Soto, Gary. (Miami, Fla. : Alfaguara : Santillana USA Pub. Co., 2006)
Collects eleven short stories focusing on the everyday adventures of Chicano young people growing up in Fresno, California.
Keywords: Mexican Americans -- California -- Fiction; Short stories; Spanish language materials